Porous silicon anodes for rechargeable metal halide batteries.

The rechargeable metal halide battery with a porous silicon anode and metal halide cathode addresses dendrite and stability issues, achieving high energy density and extended cycle life through a nitrile-based electrolyte and anodized silicon structure.

JP7601518B2Active Publication Date: 2024-12-17INTERNATIONAL BUSINESS MACHINE CORPORATION

Patent Information

Application Number
JP2022525961
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-15
Filing Date
2020-10-22
Publication Date
2024-12-17
Estimated Expiration
2040-10-22

AI Technical Summary

Technical Problem

Rechargeable batteries face limitations due to hazardous liquid electrolytes, low energy density, high cost cathode materials, dendrite formation in lithium metal anodes, and unstable solid electrolyte interfaces in silicon anodes, leading to capacity fading and limited cycle life.

Method used

A rechargeable metal halide battery design featuring a porous silicon anode and a metal halide cathode, utilizing a nitrile-based electrolyte, which includes a porous silicon anode formed by anodization to increase surface area and stability, and a metal halide as the active cathode material, allowing for high energy density and reversible charge acceptance.

Benefits of technology

The design enhances safety and longevity by preventing dendrite formation and improving cycle life, with high energy density and efficient ion transport, enabling up to 1000 charge-discharge cycles at high current densities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601518000001
    Figure 0007601518000001
  • Figure 0007601518000002
    Figure 0007601518000002
  • Figure 0007601518000003
    Figure 0007601518000003
Patent Text Reader

Abstract

The battery includes a cathode comprising a metal halide and a conductive material, the metal halide acting as the active cathode material; a porous silicon anode having a surface with pores from about 0.5 microns to about 500 microns deep, the anode comprising a metal on the surface and in at least some of the pores; and an electrolyte in contact with the anode and the cathode, the electrolyte comprising a nitrile moiety.
Need to check novelty before this filing date? Find Prior Art

Description

[Background technology]

[0001] A typical rechargeable battery is powered via electrochemical intercalation / deintercalation reactions of working ions or via conversion reactions of active electrode / electrolyte materials. In one example, lithium-ion batteries may utilize intercalated lithium compounds as electrode materials. A liquid electrolyte carries positively charged lithium ions from the anode to the cathode and vice versa. During discharge, the movement of lithium ions creates free electrons at the anode, which creates a charge on the positive current collector connected to the cathode and simultaneously generates a current through the external circuit. During charging, the reverse process occurs, and current flows from the positive current collector through the current-carrying device (cell phone, computer, etc.) to the negative current collector connected to the anode. While the battery is discharging and supplying current, the anode releases lithium ions to the cathode, generating a flow of electrons from one side to the other. When the battery is charging, lithium ions are released from the cathode and received at the anode.

[0002] Potentially harmful liquid electrolytes, as well as relatively low energy density and high cost of cathode materials, may limit the potential applications of rechargeable batteries, such as lithium-ion batteries. As an alternative to intercalated lithium anodes, lithium metal has a high energy storage capacity and has been utilized as the anode material in primary batteries. However, in some cases, lithium metal anodes may form dendrites, which may cause short circuits during battery operation. In addition, lithium metal and / or liquid electrolyte components may be flammable under some conditions when exposed to ambient conditions during use of the battery device. Also, it has proven difficult to find a suitably inexpensive cathode material that can accommodate the large amounts of lithium ions and electrons extracted from the lithium metal anode.

[0003] Silicon anodes do not generate dendrites during battery operation and can provide high energy density. However, as the battery goes through charge-discharge cycles, the volume of silicon changes significantly during the lithiation and delithiation process, which can result in particle crushing and the formation of an unstable solid electrolyte interface (SEI) layer on the electrode. The SEI layer can cause loss of electrical contact at the electrode surface, which can result in capacity fading and limit the cycle life of the battery. In addition, in some cases, silicon electrode materials may not be compatible with common electrolyte materials. Summary of the Invention

[0004] In general, the present invention is directed to a rechargeable metal halide battery comprising a porous silicon anode and a metal halide cathode. The metal halide battery has high energy density and excellent cycling behavior. The silicon anode allows for high potential for the control of lithium metal in the energy storage device, so silicon enhances safety and has a high theoretical gravimetric capacity compared to lithium metal as the anode. In one exemplary embodiment, to fabricate a porous silicon anode, a crystalline silicon substrate is anodized to provide a porous surface area, which increases the specific surface area and enhances the surface reactivity of the substrate material. The porous surface provides the silicon anode with sustainable and reversible charge acceptance and transport, improving its life extension when exposed to repeated charge-discharge cycles. In some embodiments, the porous silicon anode can be optionally plated or alloyed with other metals, such as lithium, to further improve performance.

[0005] In one aspect, the invention is directed to a battery comprising: a cathode comprising a metal halide and a conductive material, where the metal halide acts as the active cathode material; a porous silicon anode having a surface with pores from about 0.5 microns to about 500 microns deep and a metal on the surface and in at least some of the pores; and an electrolyte in contact with the anode and cathode, where the electrolyte comprises a nitrile moiety.

[0006] In another aspect, the invention is directed to a battery comprising: (a) an anode that takes up metal ions from an electrolyte during charging and releases ions to the electrolyte during discharging, the anode comprising porous silicon having pores at least 0.5 microns deep; (b) a cathode comprising a metal halide and a conductive material that function as active materials for the battery, the metal being selected from the group consisting of Li, Na, Mg, and mixtures and combinations thereof, and the halide being selected from the group consisting of I, Br, Cl, F, and mixtures and combinations thereof; and (c) an electrolyte, the electrolyte having a solvent comprising a nitrile compound.

[0007] In another aspect, the invention is directed to a method of forming a battery, comprising anodizing a crystalline Si substrate to form a porous Si anode having pores at least 500 nm deep; metallizing the porous Si anode with a metal selected from the group consisting of Li, Na, Mg, Zn, Al, and mixtures and combinations thereof; immersing the separator in an electrolyte solution comprising an active cathode material comprising a metal halide and a non-aqueous solvent comprising a nitrile compound; placing the separator immersed in the electrolyte solution between the anode and a current collector; and introducing an oxidizing gas into the stacked anode, the solution-immersed separator, and the current collector to form a battery.

[0008] The details of one or more examples of the invention are set forth in the accompanying drawings and the detailed description below. Other features, objects, and advantages of the invention will be apparent from the description and drawings, and from the claims. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a conceptual diagram illustrating an exemplary battery including an anode, an electrolyte, a current collector, and an optional separator. [Diagram 2] 1 is a schematic cross-sectional view showing a porous silicon substrate. [Diagram 3] FIG. 2 is a conceptual diagram illustrating the example battery of FIG. 1 in a closed cell. [Figure 4] (A) is a scanning electron micrograph of a cross section of prelithiated p-type porous silicon of Example 2 at an anodization current density of 5 mA / cm2 in 49% HF solution for an etching time of 1200 seconds. The dashed box highlights the approximate enlarged area shown in (B), where a ∼16 nm lithium metal layer is monolithically attached to the porous silicon electrode. [Diagram 5] 1 is a plot showing the cycle life of a lithium iodide battery with a p-type porous silicon anode (etch time: 500 seconds, anodization current density of 5 mA / cm2 in 49% HF solution). [Figure 6] 1 is a plot showing the cycle life of a lithium iodide battery with a p-type porous silicon anode (etch time: 1200 seconds, anodization current density of 5 mA / cm2 in 49% HF solution). [Figure 7] 1 is a plot showing the cycle life of a lithium iodide battery with a p-type porous silicon anode (etch time: 2400 seconds, anodization current density of 5 mA / cm2 in 49% HF solution). [Figure 8] 1 is a plot showing the cycle life of a lithium iodide battery with a bare (non-porous) pre-lithiated silicon anode, a non-anodized control sample. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Like symbols in the drawings indicate like elements.

[0011] FIG. 1 is a conceptual diagram illustrating an embodiment of a battery 10 including an anode 12, an electrolyte 14, a cathode current collector 16, an optional separator 18, and an optional anode current collector 17. Battery 10 operates via reduction-oxidation (redox) reactions, utilizing various oxidation states and redox reactions of one or more components or elements for charging and discharging. The structure shown in FIG. 1 is an exemplary embodiment and may be modified to include various shapes, sizes, scales, and the like. For example, battery 10 may be in the form of a pouch cell, a three-dimensional (3D) battery, and the like.

[0012] The anode 12, in some embodiments, comprises a porous silicon substrate that may include or consist of crystalline Si. In various embodiments, the Si substrate may be single crystal Si, multi-crystalline Si, polycrystalline Si, or mixtures and combinations thereof.

[0013] In some embodiments, the Si substrate may be optionally doped with impurities to modify the conductivity of the Si element. For example, the Si substrate may be p-type doped with elements such as boron (B), aluminum (Al), indium (In), gallium (Ga), and mixtures and combinations thereof. P-type dopants are substitutional trivalent impurities in the silicon crystal lattice, thus leaving holes in the valence band of silicon atoms in a tetravalent structure. Impurities may be incorporated into the Si substrate by a variety of techniques, including but not limited to ion implantation, epitaxial growth of Si with controlled dopant concentration, and the like.

[0014] 2, the Si substrate 120 is porous, which in this application means that the substrate 120 includes a porous region 121. Using the above conditions, the porous region 121 includes a plurality of pores 124 that extend below an exposed surface 122 of the substrate 120.

[0015] The pores 124 have an average pore diameter w of about 3 nm to about 5 nm and an average depth d of about 5 microns to about 25 microns, or about 7 microns to about 20 microns, or about 7 microns to about 13 microns from the surface 122 through the entire thickness of the porous region of the substrate 120, or from the top of the surface 122. The walls 126 between the pores 124 have an average wall thickness t of less than about 2 nm to greater than about 10 nm, or about 6 nm to about 10 nm. In some embodiments, the walls 126 have an average center-to-center distance r of about 5 nm to about 20 nm, or about 10 nm to about 20 nm, or about 12 nm to about 17 nm.

[0016] The pores 124 may be formed in the surface 122 of the Si substrate 120 by any suitable technique, such as, for example, electrochemical etching, catalytic etching, stain etching, and the like. One particularly useful technique for generating the pores 124 is an electrochemical anodization process carried out in an electrochemical cell. In one exemplary anodization process, which is not intended to be limiting, the Si substrate 120 is immersed in an electrolyte bath of concentrated hydrofluoric acid, where the Si substrate 120 forms the positive electrode and the negative electrode is a plate or rod of a material that is chemically inert to the concentrated HF bath, such as, for example, carbon, graphite, metals such as Pt, Au, and the like. In various exemplary embodiments, which are not intended to be limiting, the anodization process is carried out at a current of 0.05 mA / cm 2 ~150mA / cm 2 or 1mA / cm 2 ~10mA / cm 2 This is done using a constant current source operating at a current density of

[0017] The anodization process produces a porous region at the surface of the Si substrate with pore characteristics controlled by the anodization time. In one non-limiting example, a surface porous region having pores 124 with a depth d of about 10 μm was formed at 5 mA / cm in a HF electrolyte bath. 2 In another embodiment of the following non-limiting examples, the anodization conditions used to produce the porous region 121 are as follows: 49% HF solution, 5 mA / cm2 and the anodization current density of p-type doped silicon substrate (approximately 1 × 10 19 / cm 3 B doping) and anodization time of about 30 seconds to 40 minutes. 1 cm anodized in a concentrated HF bath at nominal room temperature (about 25 °C). 3 10 per range 19 For boron-doped Si substrates with a doping level of 5 mA / cm 2 is applied for about 1 second to about 5 hours or about 2000 seconds to about 10000 seconds. In this exemplary anodization process, pores 124 having an average depth d of about 5-6 microns from surface 122 are formed with an anodization time of 500 seconds, pores having a depth of about 7-13 microns are formed with an anodization time of 1200 seconds, and pores having a depth of about 20-25 microns are formed with an anodization time of 2400 seconds.

[0018] The walls 126 between the pores 124 have an average wall thickness t that is similarly dependent on the time and current utilized in the anodization etching process. As a non-limiting example, 5 mA / cm 2 The porous silicon substrate anodized for 200 seconds at 5 mA / cm has a pore size range of less than about 2 nm to more than about 6 nm. 2 The porous silicon substrate anodized at 500 .mu.m for 500 seconds can have a pore size range of less than about 2 nm to greater than about 10 nm.

[0019] After the anodization process, the resulting porous Si structure is optionally rinsed with deionized water and then dried.

[0020] 2, in some embodiments, the chemical and physical structure of the porous region 121 may be optionally modified by metallizing the porous Si substrate such that metal is present at the surface 122 and in at least some of the pores 124. The porous substrate 120 may be metallized by any suitable technique. For example, any suitable metal deposition technique may be used, such as atomic layer deposition (ALD), vapor deposition, electrochemical plating, and the like, although simple techniques such as direct melting alloying, in which a metal is melted and contacted with the porous substrate 120, may also be used.

[0021] Any metal or alloy, combination of metals, combination of alloys, or combination of metals and alloys may be incorporated within the pores 124. The metal, alloy, or combination selected must be capable of migrating back and forth between the battery anode and cathode in ionized form through the electrolyte medium and must have a reasonably large potential difference with the active cathode material (greater than about 1 V). Suitable examples include, but are not limited to, lithium, sodium, magnesium, zinc, aluminum, and the like. When the metallized substrate is intended for use in a lithium battery, metallization with Li has been found to be particularly useful, and such Li metallization methods are referred to herein as prelithiation.

[0022] In some embodiments, the metal 130 fills the pores 124 and forms a metal region 132 having a substantially planar metal surface 134. In some embodiments, the metal region has a metal concentration gradient, with the metal concentration being highest near the surface 134 and gradually decreasing in the pores 124. The porous region 121 of the Si substrate 120 and the crystalline region 136 of the Si substrate directly beneath the porous region 121 are electrically, physically, and chemically interconnected to form a monolithic structure. In some embodiments, a smooth surface is not required for efficient cell operation, but a smooth metal surface 134 is preferred. 134 is very smooth, with a root mean square (RMS) surface roughness of less than about 10 angstroms (Å), or less than 5 Å, or less than about 3 Å. In some exemplary, non-limiting embodiments, the metal surface 134 has a height h from the surface 122 of about 10 nm to about 100 nm, about 10 nm to about 50 nm, or about 10 nm to about 20 nm.

[0023] The anode 12 takes up metal ions from the electrolyte 14 during charging and releases metal ions to the electrolyte 14 during discharging. The electrolyte 14, which may be aqueous or non-aqueous, includes a solvent, a metal halide, and an optional oxidizing gas. The solvent in the electrolyte 14 may be selected to further enhance the electrochemical performance of the battery 10, such as by improving rechargeability, cyclability, electrode structure, or the like. In various embodiments, which are not intended to be limiting, suitable solvents may be selected from non-aqueous organic solvents such as ethers, glymes, carbonates, nitriles, amides, amines, organosulfur solvents, organophosphorus solvents, organosilicon solvents, fluorinated solvents, adiponitrile (ADN), propylene carbonate (PC), dimethoxyethane (DME), and mixtures and combinations thereof. In some embodiments, non-aqueous solvents including nitrile compounds have been found to be particularly useful.

[0024] In some embodiments, electrolyte 14 may include an optional heterocyclic compound, which as used herein refers to an aromatic or non-aromatic cyclic compound having atoms of at least two different elements as ring members. A cyclic compound (ring compound), as used herein, refers to a compound in which one or more series of atoms in a compound are bonded to form a ring. In various embodiments, suitable cyclic compounds for electrolyte 14 include five-membered rings such as pyrrolidone, oxolane, thiolane, pyrrole, furan, and thiophene; six-membered rings such as piperazine, oxane, thiane, pyridine, pyran, and thiopyran; and seven-membered rings such as azepane, oxepane, thiepane, azepine, oxepine, and thiepine. Examples of suitable heterocyclic compounds include, but are not limited to, tetrahydrofuran, tetrahydropyran, tetrahydrothiophene, oxathiolane, succinimide, oxazolidone, γ-butyrolactone, γ-caprolactone, ε-caprolactone, γ-valerolactone, pyrrolidine, imidazolidine, sulfolane, thiane, and mixtures and combinations thereof. In some embodiments, suitable heterocyclic compounds include, but are not limited to, cyclic ethers, cyclic esters, and mixtures and combinations thereof.

[0025] The electrolyte 14 also includes a metal halide (e.g., MX, where M is a metal element and X is a halogen element) that provides ionic conductivity to the electrolyte 14. In some examples, the metal halide includes an electrolyte salt that dissociates into halide ions and metal ions. For example, the metal halide can dissolve in a solvent of the electrolyte 14 and dissociate into its metal and halide ions. In some examples, which are not intended to be limiting, the halide ions can include at least one ion of I, Br, Cl, or F (e.g., X can be I, Br, Cl, or F), and the metal ions can include at least one ion of Li, Mg, or Na (e.g., M can be Li, Mg, or Na).

[0026] In some embodiments, the electrolyte 14 includes an optional additional salt that dissociates into metal ions and counter anions. In some non-limiting examples, the metal ions include at least one of Li, Mg, and Na, and the counter anions include nitrate anions (NO3 - ), hexafluorophosphate anion (PF6 - ), tetrafluoroborate anion (BF4 - ), Bis(oxalato)borate anion (BOB - ), difluorooxalatoborate anion (DFOB - ), trifluoromethanesulfonate anion (TF - ) and trifluorosulfonylimide anion (TFSI - )

[0027] In some embodiments, the metal halide of the electrolyte 14 functions as an active cathode material that receives, stores, and releases its metal ions during charging and discharging of the battery 10. Thus, the battery 10 lacks a dedicated cathode material and relies on the active cathode material of the metal halide of the electrolyte 14 and the current collector 16 for ion transport. By extension, the battery 10 may be cheaper to manufacture, may be lighter, may have a high power density, or a combination thereof. In some cases, the high power density of an electrolyte that includes a metal halide that functions as an active cathode material may allow the battery 10 to be charged significantly faster than some other batteries that do not include the electrolytes described herein. In some examples, an electrolyte lacking a metal halide may reduce electrochemical performance (e.g., reversibility, rechargeability, and / or cyclability) compared to an electrolyte 14 that includes a metal halide, may generate irreversible carbonate by-products, may reduce power density, or a combination thereof.

[0028] In some embodiments, the electrolyte 14 may include or be in the presence of an optional oxidizing gas, and as used herein, "including an oxidizing gas" is intended to include either configuration. In some examples, the oxidizing gas may be dissolved in a solvent of the electrolyte 14. In some examples, which are not intended to be limiting, the oxidizing gas includes at least one of oxygen, air, nitric oxide, or nitrogen dioxide. The oxidizing gas may help induce the redox reactions of the battery 10 described above and help achieve highly reversible redox reactions, which may contribute to improved electrochemical performance of the battery 10. The oxidizing gas may help induce such redox reactions, but is not consumed or released during use of the battery 10 (e.g., the oxidizing gas does not participate in the redox reactions of the battery 10). In some examples, an electrolyte that includes a metal halide and a solvent but does not include an oxidizing gas may exhibit little or no rechargeability.

[0029] The current collectors 16-17 may comprise any material having suitable electrical conductivity to collect electrons generated by redox reactions during discharge of the battery 10 and provide a conductive path to an external electronic circuit to which the battery 10 is connected. Similarly, during recharge of the battery 10, the current collectors 16-17 provide an electrical path between an external voltage source and the electrolyte 14 to supply a voltage for another redox reaction to charge the battery 10. In some examples, the current collectors 16-17 may comprise conductive powders, such as metal or carbon powders or both, woven or non-woven metal fibers, metal foams, woven or non-woven carbon fibers, or the like. In some embodiments, the current collectors 16-17 may comprise stainless steel mesh, aluminum (Al) mesh, nickel (Ni) foam, or carbon paper, or combinations thereof. For example, in one embodiment, one or both of the current collectors 16-17 comprise stainless steel mesh having carbon nanoparticles deposited thereon. As yet another example, one or more of the current collectors 16-17 may be a conductive porous material.

[0030] In other examples, the battery 10 may include an optional, specialized cathode material 15 in addition to the metal halide that functions as the active cathode material. For example, the battery 10 may include a cathode 15 that provides a conductive path to an external electrical circuit to which the battery 10 is connected. In some cases, the battery 10 may include a cathode that can be used in Li-ion batteries. For example, the cathode may be a lithium cobalt oxide (LCO, e.g., LiCoO), nickel cobalt aluminum (NCA, e.g., LiNi x Co y Al z O2, LiNi 0.8 Co 0.15 Al 0.05 O2), lithium manganese oxides (LMOs, e.g. LiMn2O4), lithium manganese oxyfluorides (LMOFs), lithium nickel manganese cobalt oxides (NMCs, e.g. LiNiMnCoO2), nickel cobalt manganese (NCMs, e.g. LiNi x Co y Mn z O2, LiNi 0.33 Co 0.33 Mn0.33 O2) or lithium iron phosphate (LFP, e.g., LiFePO4).

[0031] In some examples, the battery 10 includes an optional separator 18. The separator 18 prevents physical contact between opposing electrodes, thereby preventing shorting of the battery by preventing transport of electrons through the entire internal circuit such that electrons do not move through the battery 10 (e.g., through the electrolyte 14 of the battery 10) while still allowing metal ions to flow through the battery 10 during charging and discharging. In some examples, the separator 18 may be immersed in, within, surrounded by the electrolyte 14, or the like. In various embodiments, the separator 18 includes an electrically non-conductive material to prevent the movement of electrons through the battery 10 such that the electrons would instead move through the external circuit. In some non-limiting examples, the separator 18 may be made of glass, non-woven fibers, polymeric films, rubber, or the like.

[0032] In some examples, battery 10 is contained in a closed or substantially closed cell or enclosure. In this manner, the oxidizing gas of electrolyte 14 remains within battery 10 such that battery 10 has a relatively fast charge rate, high energy efficiency, high power density, high reversibility, high cyclability, or a combination thereof, as described herein.

[0033] In some embodiments, battery 10 may be capable of undergoing many charge / discharge cycles even at relatively high charge densities (e.g., exhibiting good rechargeability). In some examples, battery 10 has a current density of about 1 mA / cm 2 , about 5mA / cm 2 , about 10mA / cm 2 or about 20mA / cm 2 At least 100 charge / discharge cycles can be completed at a current density of about 1 mA / cm. 2 , about 5mA / cm 2 , about 10mA / cm2 or about 20mA / cm 2 At the above current density, it may be possible to complete at least 1000 charge / discharge cycles.

[0034] In embodiments in which the anode is a crystalline Si substrate metallized by anodization, in some non-limiting examples, the ratio of the average cycle life of battery 10 in number of charge / discharge cycles to the anodization time is about 2 or more, or about 6 or more, or about 12 or more.

[0035] In some embodiments, the battery 10 exhibits relatively high energy efficiency. For example, the battery 10 exhibits a current density of about 1 mA / cm 2 , about 5mA / cm 2 , about 10mA / cm 2 or about 20mA / cm 2 In some examples, the battery 10 may exhibit energy efficiencies of 90% or more at current densities of about 1 mA / cm 2 , about 5mA / cm 2 , about 10mA / cm 2 or about 20mA / cm 2 At current densities above this, it is possible to achieve an energy efficiency of over 99%.

[0036] 3 is a conceptual diagram illustrating the exemplary battery 10 of FIG. 1 within an enclosed cell system 20. The enclosed cell system 20 may include cells that house the battery 10 during operation, cells used to make the battery 10, or both. For example, the closed cell system 20 may include cells available under the trade name SWAGELOK from Swagelok of Solon, Ohio, and may be used to make the battery 10. In some examples, the closed cell system 20 may include an inlet tube 22 or an outlet tube 24, or both. The inlet tube 22 and the outlet tube 24 may be used to introduce and remove air or other gases, such as oxidizing gases of the electrolyte 14, into and out of the enclosed cell.

[0037] In one example, to make the closed cell system 20 of Figure 3, a metal halide is dissolved in a solvent to form a solution. To dissolve the metal halide in the solvent, the metal halide may be added to the solvent and gently stirred, such as gently stirred overnight. In some examples, the solution of the metal halide dissolved in the solvent has a concentration of about 0.1M to about 20M, about 0.5M to about 10M, or about 1M to about 5M.

[0038] In some examples, the metal halide may be dried before being dissolved in a solvent. The drying temperature and / or drying time may be selected based on the metal halide used in electrolyte 14, and in some non-limiting examples, the metal halide may be dried at about 120° C. on a hot plate in an argon-filled glove box for more than 12 hours.

[0039] The optional separator 18 is then immersed in the electrolyte solution, for example by dipping. In some examples, immersing the separator 18 in the solution may result in the separator 18 being immersed in approximately 1 μL / cm 2 ~Approx. 500μL / cm 2 , about 10μL / cm 2 ~Approx. 250μL / cm 2 or about 50 μL / cm 2 ~Approx. 100μL / cm 2 The method may include immersing the substrate in a solution of

[0040] The anode 12, optional submerged separator 18, and current collector 16 may then be stacked together in a closed cell system 20. In some examples, the stacking process may include placing the separator 18 between the anode 12 and the current collector 16. In some examples, one or more of the anode 12, submerged separator 18, and current collector 16 may be stacked prior to submerging the separator 18 in the solution. For example, the separator 18 may be stacked on the anode 12 and then submerged in the solution. In some cases, the closed cell system 20 may be at least partially open during the stacking procedure, and after the anode 12, submerged separator 18, and current collector 16 are stacked, the closed cell system 20 may be closed or substantially closed to form a closed or substantially closed volume around the anode 12, submerged separator 18, and current collector 16.

[0041] An oxidizing gas may optionally be introduced into the closed cell system 20. In some examples, the oxidizing gas may be introduced into the closed cell system 20 through the inlet tube 24. In some examples, the closed cell system 20 may contain or be in the presence of an inert gas, such as argon, prior to introducing the oxidizing gas into the closed cell system 20. In some such examples, the introduction of the oxidizing gas may purge and completely replace the inert gas in the closed cell system 20 with the oxidizing gas. For example, the oxidizing gas may be introduced into the closed cell 20 through the inlet tube 24 and the inert gas may be purged through the outlet tube 26. In some examples, the concentration of the oxidizing gas in the closed cell system 20 may be about 5 weight (wt)% to about 100 wt%, about 50 wt% to about 100 wt%, or about 80 wt% to about 100 wt% of the total amount of gas in the closed cell system 20, such as the total amount of oxidizing gas and inert gas in the closed cell system 20. The invention will now be described with reference to the following non-limiting examples. EXAMPLES

[0042] Example 1

[0043] Preparation of porous Si The anodization process was carried out by immersing a boron-doped (p-type) crystalline silicon substrate approximately 700 microns thick into a solution of concentrated HF (49%). An electrical bias is then applied to the substrate against a Pt electrode also placed in the solution. The p-type doped Group IV semiconductor material layer acted as the positive electrode, and the Pt electrode acted as the negative electrode.

[0044] The anodization method of Example 1 was carried out at about 5 mA / cm 2 The anodization was performed using a constant current source operating at a current density of about 9.3 μm. The current density of Example 1 was applied at room temperature (25° C.) for about 1200 seconds to provide pores in the surface porous region with a depth of about 9.3 μm. After the anodization process, the porous structure was rinsed with deionized water and then dried. Example 2

[0045] Prelithiation of porous silicon. The porous silicon anode of Example 1 was prelithiated and metallized using a direct melt alloying method. Lithium metal was heated on a hot plate at 160°C to 190°C to allow the lithium metal to reach a molten state. The surface of the porous silicon was then brought into intimate contact with the molten lithium metal for about 30 seconds. Unreacted Li metal was then removed from the surface of the porous silicon.

[0046] The method produced a very smooth (<5 Angstroms root mean square roughness) and planar lithiated surface as shown in FIG. 4(A), where the contrast between porous and crystalline silicon is highlighted by the scale bar illustrating a porous silicon region of about 9.3 μm. A magnified structure of the surface region (dashed box) of FIG. 4(A) is shown in FIG. 4(B), where a layer containing primarily lithium metal of about 16 nm is visible.

[0047] As can be seen from the color contrast of the SEM (secondary electron microscope) cross-section, a decrease in the lithium concentration was observed at depth below the Li-rich surface region. All regions, including the Li-rich surface, the porous Si, and the crystalline Si immediately below the porous Si, were electrically, physically, and chemically connected and integrated with the crystalline silicon substrate. Example 3

[0048] Electrolyte preparation and cell assembly Lithium iodide (LiI) was placed in a vial and dried at 120 °C on a hot plate in an argon-filled glove box (<0.1 ppm H2O and O2) for 1 h. 3-Methoxypropionitrile (MPN) was purified overnight over molecular sieves (3 Å). 1 M of dry LiI was added and dissolved in MPN and gently stirred overnight.

[0049] Porous silicon anodes were prepared by chemical etching of crystalline silicon wafers and subsequent prelithiation as described above in Examples 1-2. The depth of the porous region in the wafer was determined by the amount of etching time.

[0050] The resulting solution was used to immerse a separator on top of a metallized porous silicon anode, and a cathode current collector was placed on top of the separator. The cathode current collector comprised porous carbon and a polymer binder in a weight ratio of about 8:1.

[0051] The separator wetted with electrolyte solution was placed between the porous silicon anode and the cathode current collector, and was in contact with both the porous silicon anode and the cathode current collector. Assembly of the cell with the cell components including the porous silicon anode, the separator wetted with electrolyte solution, and the cathode current collector was carried out in an argon filled glove box (<0.1 ppm H2O and O2). All the cell components were placed in a Swagelok type cell with both inlet and outlet tubes for gas flow. Example 4

[0052] Rechargeable lithium iodide battery with porous silicon anode (Etching time: 500 seconds) Figure 5 shows the current density of 5mA / cm 2FIG. 1 is a plot of the cycle number of a rechargeable lithium iodide battery with a porous silicon anode versus specific capacity at a current density of 1000 s. The etching time was recorded as 500 s, which, as discussed above, determines the depth of the porous region formed in the crystalline silicon anode, with increasing etching time providing deeper pores in the porous region. The specific discharge capacity was approximately 0.7 mAh / cm for the first cycle. 2 and in the next cycle it starts at about 1.0 mAh / cm 2 and continued until about the 50th cycle. Example 5

[0053] Rechargeable lithium iodide battery with porous silicon anode (Etching time: 1200 seconds) Figure 6 shows the current density of 5mA / cm 2 FIG. 1 is a plot of the cycle number of a rechargeable lithium iodide battery with a porous silicon anode versus specific capacity at a current density of 1000 s. The etching time was recorded as 1200 s. The specific discharge capacity was approximately 0.5 mAh / cm for the first cycle. 2 and in the next cycle it starts at about 1.0 mAh / cm 2 and continued until about the 250th cycle. Example 6

[0054] Rechargeable lithium iodide battery with porous silicon anode (Etching time: 2400 seconds) Figure 7 shows the current density of 5mA / cm 2 FIG. 1 is a plot of the specific capacity at a current density of 1000 s vs. the cycle number of a rechargeable lithium iodide battery with a porous silicon anode. The etching time was recorded as 2400 s. The specific discharge capacity was approximately 0.5 mAh / cm for the first cycle. 2 and in the next cycle it starts at about 1.0 mAh / cm 2 and continued until about the 500th cycle.

[0055] Comparative Example 1 Rechargeable lithium iodide battery with non-porous silicon anode Figure 8 shows the current density of 5mA / cm 2 FIG. 1 is a plot of the cycle number of a rechargeable lithium iodide battery with a bare (non-porous) silicon anode versus specific capacity at a current density of 1000 s. The etch time was recorded as 0 seconds indicating that the anode contained no porous regions. The bare (non-porous) silicon anode was prelithiated in the same manner as described in Examples 4-6 above. The specific discharge capacity was approximately 0.6 mAh / cm on the first cycle. 2 and in the next cycle it starts at about 0.9 mAh / cm 2 and continued until approximately the 20th cycle.

[0056] Various embodiments are described herein. These and other embodiments are within the scope of the following claims.

[0057] In a preferred embodiment of the present invention, a battery is provided, comprising: (a) an anode that takes up metal ions from an electrolyte during charging and releases ions to the electrolyte during discharging, the anode comprising porous silicon with pores at least 0.5 microns deep; (b) a cathode comprising a metal halide and a conductive material that serves as an active material for the battery, the metal in the metal halide being selected from the group consisting of Li, Na, Mg, and mixtures and combinations thereof, and the halide being selected from the group consisting of I-, Br-, Cl-, F-, and mixtures and combinations thereof; and (c) an electrolyte, the electrolyte comprising a solvent comprising a nitrile compound. Preferably, the battery further comprises a separator between the anode and the cathode. The electrolyte preferably comprises a solvent selected from the group consisting of ethers, glymes, carbonates, amides, amines, organosulfur solvents, organophosphorus solvents, organosilicon solvents, fluorinated solvents, heterocyclic solvents, and mixtures and combinations thereof. The battery preferably includes an oxidizing gas selected from the group consisting of air, oxygen, nitric oxide, nitrogen dioxide, and mixtures and combinations thereof. The battery preferably includes a second cathode in addition to the metal halide that functions as the active cathode material. The anode preferably includes a metal layer that covers the pores. The metal layer preferably has an RMS surface roughness of less than about 5 Angstroms.

Claims

1. A battery, a cathode current collector; a porous silicon anode having a surface with pores having a depth of 0.5 microns to 500 microns and containing a metal on said surface and in at least some of said pores; an electrolyte in contact with the anode and the cathode current collectors and comprising a metal halide and a nitrile compound that serves as an active cathode material; Including, The battery, wherein the metal is selected from the group consisting of Li, Na, Mg, Zn, Al, and mixtures and combinations thereof.

2. 10. The battery of claim 1, wherein the metal comprises a layer having an RMS surface roughness of less than 5 Angstroms.

3. 10. The battery of claim 1 , wherein the anode comprises crystalline Si.

4. 10. The battery of claim 1, wherein the anode is doped with a metal selected from the group consisting of B, Al, In, Ga, and mixtures and combinations thereof.

5. 10. The battery of claim 1, further comprising a separator between the anode and the cathode current collector.

6. 10. The battery of claim 1, wherein the electrolyte comprises an ionically conductive material.

7. 10. The battery of claim 1, wherein the battery comprises an oxidizing gas selected from the group consisting of oxygen, air, nitric oxide, nitrogen dioxide, and mixtures and combinations thereof.

8. 2. The battery of claim 1, wherein the electrolyte comprises a solvent selected from the group consisting of ethers, glymes, carbonates, amides, amines, organosulfur solvents, organophosphorus solvents, organosilicon solvents, fluorinated solvents, heterocyclic solvents, and mixtures and combinations thereof.

9. 2. The battery of claim 1, wherein the metal halide comprises an electrolyte salt that dissociates in a solvent into halide ions and metal ions, the halide ions comprising at least one ion of I, Br, Cl, and F, and the metal ions comprising at least one ion of Li, Mg, and Na.

10. The method further comprises the step of: providing a solution of a compound having a metal ion and a counter anion, the metal ion being selected from the group consisting of Li, Mg, and Na, and mixtures and combinations thereof, the anion being nitrate (NO 3 - ), hexafluorophosphate anion (PF 6 - ), tetrafluoroborate anion (BF 4 - ), bis(oxalato)borate anion (BOB - ), difluorooxalatoborate anion (DFOB - ), trifluoromethanesulfonate anion (TF - ), trifluorosulfonylimide anion (TFSI - 10. The battery of claim 9, wherein the compound is selected from the group consisting of:

11. 10. The battery of claim 1 further comprising a specialized cathode material in addition to said active cathode material comprising said metal halide.

12. 1. A method of forming a battery, comprising: anodizing a crystalline Si substrate to form a porous Si anode having pores at least 500 nm deep; metallizing the porous Si anode with a metal selected from the group consisting of Li, Na, Mg, Zn, Al, and mixtures and combinations thereof; immersing the separator in an electrolyte solution comprising an active cathode material comprising a metal halide and a non-aqueous solvent comprising a nitrile compound; placing the separator, soaked in the electrolyte solution, between the anode and a current collector; directing an oxidizing gas through the stacked anode, the separator soaked in the solution, and the current collector to form the battery; A method comprising:

13. The method of claim 12, wherein the porous Si anode comprises a Li metal layer.

14. The method of claim 13 , wherein the layer has an RMS surface roughness of less than 5 Angstroms.

15. 13. The method of claim 12, wherein the porous Si anode is doped with a metal selected from the group consisting of B, Al, In, Ga, and mixtures and combinations thereof.

Citation Information

Patent Citations

  • Nonaqueous electrolyte battery

    JP2009064584A

  • Method of manufacturing porous silicon

    JP2010251647A

  • Structured silicon battery anode

    JP2013509687A

  • High-capacity anode materials for lithium-ion batteries

    JP2013510405A

  • Usage of nonaqueous electrolyte battery, and nonaqueous electrolyte battery

    JP2014011105A

Cited By

  • Multilayer body, electronic device, and method of producing multilayer body

    US12761081B2

  • Multilayer body, electronic device, and method of producing multilayer body

    US20240011840A1